상업 정보 계열 고등학교 암호 교육 프로그램 개발 및 적용에 관한 연구 - 박중수; 정상조 (韓國學校數學會論文集, 2009)
The purpose of this study is to develop a contents when we are going to introduce cryptography and information security for vocational high school students. For this we do a survey of the students' level for understanding of information security and the 7th curriculum for school mathematics, 2007 revised curriculum for school mathematics, the curriculum for vocational high school, and we search for the material that connects between mathematics subjects and vocational subjects. We develop a text book that introduces information security and cryptography. After we teach vocational high school students by using this developed book, we get the result that learning cryptography with computer programming makes a good motivation of learning mathematics and roles a parameter between mathematics curriculum and vocational curriculum. As a result we propose that the developed contents can be used in 'Practical Mathematics' in the 7th curriculum for school mathematics or 'Application of Mathematics' in 2007 revised curriculum for school mathematics. 본 논문은 암호 및 정보보호와 관련된 내용들을 상업 정보 계열 고등학교 학생들에게 소개하고자 할 때, 사전에 학생들의 정보화 수준 및 암호와 정보보호의 이해에 대한 실태를 파악하고, 제7차 수학과 교육과정과 2007 개정 수학과 교육과정 및 상업 정보 계열 고등학교 전문 교과 교육과정을 검토하여 수학 교과와 전문 교과 사이의 연관성을 파악함으로써, 상업 정보 계열 고등학교에서 수업 시간에 활용할 수 있는 교재를 개발하고 이를 실제 수업에 적용한 결과에 대한 분석이다. 개발된 교재를 사용하여 상업 정보 계열 고등학교 학생들에게 암호 기초 이론을 강의하고 관련 알고리즘을 프로그래밍 언어를 사용하여 프로그래밍하게 한 결과 암호 학습이 수학학습의 동기 유발은 물론이고 수학 교과와 전문 교과 사이의 매개역할을 할 수 있는 것으로 조사되었고, 이러한 결과를 토대로 프로그래밍 실습을 포함한 암호 학습을 제7차 수학과 교육과정의 '실용수학' 또는 2007 개정 수학과 교육과정의 '수학의 활용'에 추가할 것을 제안하였다.